2018
DOI: 10.1016/j.ecoenv.2017.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Selenite-induced nitro-oxidative stress processes in Arabidopsis thaliana and Brassica juncea

Abstract: Extremes of selenium (Se) exert toxic effects on plants' physiological processes; although plant species tolerate Se differently. This study focuses on the effect of Se (0, 20, 50 or 100μM sodium selenite) on secondary nitro-oxidative stress processes mainly using in situ microscopic methods in non-accumulator Arabidopsis thaliana and secondary Se accumulator Brassica juncea. Relative Se tolerance or sensitivity of the species was evaluated based on growth parameters (fresh and dry weight, root growth) and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…significantly has been reported to reduce metal accumulation with growth improvement, which also ensures better crop productivity and health benefits to consumers (Pandey and Gupta, 2018). It is also reported that, excessive concentration of Se is also toxic for plants by causing chlorosis, growth reduction, and even oxidative stress (Molnár et al, 2018;Hasanuzzaman et al, 2020); that is why it is imperative to emphasize selecting the optimal dose of Se. Therefore, extensive and broad scale research is still required for determining the crucial dose and engagements of Se for attaining plant tolerance toward metals.…”
Section: Introductionmentioning
confidence: 99%
“…significantly has been reported to reduce metal accumulation with growth improvement, which also ensures better crop productivity and health benefits to consumers (Pandey and Gupta, 2018). It is also reported that, excessive concentration of Se is also toxic for plants by causing chlorosis, growth reduction, and even oxidative stress (Molnár et al, 2018;Hasanuzzaman et al, 2020); that is why it is imperative to emphasize selecting the optimal dose of Se. Therefore, extensive and broad scale research is still required for determining the crucial dose and engagements of Se for attaining plant tolerance toward metals.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to B. juncea, the selenium sensitive Arabidopsis thaliana exhibited pronounced oxidative stress and was accompanied by slight modifications in protein nitration; Brassica juncea exhibited moderate oxidative and intense nitrosative stress. The results of this comparative study suggest that selenite tolerance or sensitivity is more associated with oxidative processes than secondary nitrosative modifications in the above plant species (Molnár et al, 2018b). Recently, nitrosative and oxidative processes were examined in Se hyperaccumulator and non-accumulator Astragalus species in order to evaluate the possible role of RNS metabolism and signaling in Se (hyper)tolerance (Kolbert et al, 2018).…”
Section: A C C E P T E Dmentioning
confidence: 97%
“…Molnár et al ( 2018) demonstrated that selenite-induced cell wall alterations and stomatal regulations in Arabidopsis were associated with lower stomatal density and that selenite sensitivity resulted in the stomatal opening, callose aggregation, serious oxidative stress, and moderate nitrosative modifications in plants. The Se-induced photosynthesis dysfunction is widely regarded as the most important cause of increased accumulation of ROS and oxidative stress, and it is widely recognized as one of the most important mechanisms of Se phytotoxicity [32].…”
Section: Harmful Effects Of Selenium In Plantsmentioning
confidence: 99%
“…In terms of biological processes and yield in the soil and plants, the application of Se in standard fertilizer form is deemed less efficient than the application of SeNPs in standard fertilizer form [46]. Specifically, it has been found that Se can ease stress in plants because it causes the manufacture of secondary metabolites and increases the activities of antioxidant enzymes according to the literature [32]. To mitigate multiple kinds of abiotic stress, including extremely high temperatures, droughts, heavy metal accumulation, and salt, the usage of SeNPs is increasingly popular and is becoming increasingly important.…”
Section: Fertilizer For Cropsmentioning
confidence: 99%